In-service middle school teachers' cognition in the use of technology in English as a second language (ESL) teaching and learning context in Dingxi City, China - Wei, Wenyang; Abdullah, Nur Surayyah Madhubala; Nordin, Nooreen (Sciedu Press, 2022)
Many in-service ESL teachers have low interest in using technology in classrooms on account of complex internal and external factors. Thus, guided by Davis’s (1989) technology acceptance model and Borg’s (2003) language teacher cognition theory, this study, which uses a quantitative descriptive survey, aims to further understand in-service middle school English as a second language (ESL) teachers' cognition in the use of technology in Dingxi city, China. The results show that in-service middle school ESL teachers have general positive cognition toward technology in their classrooms and that these teachers are high-level users of technology. The findings suggest that academic institutions can provide more decent technological support to in-service middle school teachers as this will cater to their needs in ESL teaching and learning.